Incidence of critical events in the post-anesthesia care unit at a resource-limited setting in Debre Markos, Northwest Ethiopia - Abebaw Misganaw; Alaye Debas Ayenew; Netsanet Temesgen Ayenew; Enyew Fenta Mengistu; Baye Ashenef; Samrawit Nega Shiferaw; Getamesay Demelash Simegn (PLoS ONE, 2026)
Background Surgery and anesthesia can disrupt normal physiological function through surgical stress and residual anesthetic effects, increasing the risk of post-anesthetic complications, known as critical incidents. This study aimed to determine the incidence of critical events in the post-anesthesia care unit at Debre Markos Comprehensive Specialized Hospital, Ethiopia. Methods An institution-based prospective cross-sectional study was conducted from June 1, 2024, to September 30, 2024. The sample size was determined by a single proportion formula using a prevalence of 50% and a 5% margin of error at the 95% confidence interval. The data was analyzed using SPSS version 22 for windows. Analysis was conducted using bivariable and multivariable logistic regression as needed. Result Of the 422 patients, 160 (37.9%) experienced one or more critical events, with a total of 214 complications recorded. The most common critical events that occurred in the PACU were cardiovascular-related events (42%) and respiratory & airway related incidents (20%). BMI, duration of anesthesia, intraoperative complications, patient handover, PACU staff training, and ASA physical status were significantly associated with the occurrence of critical events. The odds of critical events were higher among underweight (AOR = 3.71; 95% CI: 1.27–10.79) and overweight patients (AOR = 3.05; 95% CI: 1.28–7.24). Anesthesia duration of 1–2 hours (AOR = 2.01; 95% CI: 1.06–3.81) and >2 hours (AOR = 4.11; 95% CI: 1.59–10.66) also increased the risk. Patients with intraoperative complications had higher odds of critical events (AOR = 3.52; 95% CI: 1.88–6.58), as did those without proper handover (AOR = 3.92; 95% CI: 2.11–7.25). Increasing ASA class was associated with higher risk ASA II (AOR = 2.59; 95% CI: 1.11–6.07), ASA III (AOR = 2.86; 95% CI: 1.20–6.86), and ASA IV (AOR = 11.75; 95% CI: 2.76–50.03). Additionally, patients cared for by PACU nurses without prior PACU training were more likely to develop complications (AOR = 3.15; 95% CI: 1.73–5.72). Conclusion Approximately 38% of patients experienced ≥1 critical event, mainly cardiovascular and respiratory complications. Patients who had intraoperative complications, ASA 2 to ASA 4 status, under/overweight, and those who received anesthesia for a prolonged duration were relatively at higher risk of developing critical events. There was a long time to stay in the PACU for those patients who experienced critical events.